Evaluation of Fibre Migration Angle by Image Processing Using Economic Usb Camera and Matlab: Demonstrated Example. (2015) - Khandual, A.; Luximon, A.; Rout, N.; Grover, T.; Kandi, I.M.
Abstract: An internal arrangement of fibres in the yarn plays a key role in determining the physical properties and the performance characteristics of yarns and fabrics. Crosswise and lengthwise fiber migration and twist are important components to generate strength and cohesion in yarns. Their objective study is becoming essential as various new yarns has been developed with dissimilar properties and they are blended frequently. In addition, many modern techniques of spinning coming up since last few decades. Though new equipment and image processing techniques has been reported by few scientists, it is still jargon for new researchers to apply it for their own investigation. We demonstrated here how image processing technique in MATLAB could be employed by taking tracing fibre images from economic USB camera to evaluate tracing fibre angle accurately. This non-destructive evaluation method could potentially be applied in various fields of biomedical imaging, material engineering and other photogrammetric applications.